A womanist reading of Hebrew Bible narratives as the politics of belonging from an outsider within - Lovelace, Vanessa (Womanist readings of scripture, 2024)
"Vanessa Lovelace uses an intersectional lens of race/ethnicity, gender, and sexuality and nation to explore how both biblical authors and U.S. antebellum and early twentieth century White supremacists used exclusionary political processes to include some and exclude others as members of the nation, especially the politicization of motherhood"--